Do We Need Basic Research in Cardiac Surgery? - Doenst, Torsten; Schlensak, Christian; Schibilsky, David; Faerber, Gloria (The Thoracic and Cardiovascular Surgeon, 2018)
Thinking about the daily practice of cardiac surgery, genetically altered mouse models, polymerase chain reactions, western blots, and other laboratory tools are the last that comes to mind. It is, therefore, not surprising that the pursuit of such basic science activities by practicing surgeons and those in training is often limited. However, there is an innate connection between these two seemingly different disciplines. To address and visualize this connection, we propose the following three hypotheses. First, cardiac surgery would not be at its present level of expertise without fundamental contributions of basic science. Second, without practicing cardiac surgeons performing basic research and translating their results to clinical practice next to their daily work, our ability to care for cardiac surgery patients would be poorer. Third, basic science training for those aiming to become practicing cardiac surgeons improves their ability to properly care for their patients. Finally, we will discuss some potentially even unexpected implications for our currently changing daily clinical practice.
Keywords: basic science; cardiac surgery; clinical care; cardiac surgeons